2021
DOI: 10.46281/afbr.v5i1.1009
|View full text |Cite
|
Sign up to set email alerts
|

The Determinance of the Financial Behavior Among Graduate Students in Indonesia

Abstract: The lifestyle of adolescents who migrate to work and college will largely determine their future. Concerns about economic conditions can cause problems with their behavior. This research has aimed to explore the most influential factors on Financial Behavior among graduate students in Indonesia. The Primary data collected by distributing questionnaires using a Likert scale. There are 239 samples have collected based on the combination of purposive and convenience sampling methods. The study used descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…These results are according to the studies of Sam et al, (2022), Pamikatsih et al, (2022), Adiputra et al, (2021), Wiyanto et al, (2019 that the effect of positive financial knowledge is significant on financial behavior. In a direction according to Nyoto et al, (2021); Patricia and Nuringsih (2022) although the results are not significant. Financial knowledge increases the ability to plan finances to avoid financial problems.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These results are according to the studies of Sam et al, (2022), Pamikatsih et al, (2022), Adiputra et al, (2021), Wiyanto et al, (2019 that the effect of positive financial knowledge is significant on financial behavior. In a direction according to Nyoto et al, (2021); Patricia and Nuringsih (2022) although the results are not significant. Financial knowledge increases the ability to plan finances to avoid financial problems.…”
Section: Discussionmentioning
confidence: 73%
“…Wiyanto et al, (2019) stated that limited financial knowledge has an impact on poor financial planning so that this knowledge is a basic need for an individual to avoid financial problems. Nyoto et al, (2021); Patricia and Nuringsih (2022) did not prove a significant effect of financial knowledge on financial behavior, whereas Pamikatsih et al, (2022), Adiputra et al, (2021) produced a significant effect on financial behavior. In accordance with Generation Z, the formulation of first hypothesis is: Ha1: Financial knowledge has a positive effect on financial behavior in Generation Z…”
Section: Financial Knowledgementioning
confidence: 79%
“…Meanwhile, according to (Suwatno, 2014) job satisfaction is a worker's feelings towards his work, whether he likes or likes or dislikes or dislikes as a result of the interaction of workers with work environment or as a perception of mental attitude, as well as the result of workers' assessment of their work. Workers' feelings towards their work reflect their attitude and behavior (Nyoto, Renaldo, Karuppannan, Bhuiyan, & Kumarasamy, 2021) at work.…”
Section: Literature Review Employee Performance Theorymentioning
confidence: 99%
“…Based on the description above, it can be concluded that buying interest arises because of a learning process that creates a motivation in consumers to fulfill their needs and is a psychological aspect that influences the attitudes and behavior (Nyoto, Renaldo, Karuppannan, Bhuiyan, & Kumarasamy, 2021) of consumers to buy a product which is influenced by the information it receives.…”
Section: Interestmentioning
confidence: 99%